Species of Syllis Savigny in Lamarck, 1818 (Polychaeta: Syllidae) living in corals in the state of São Paulo, southeastern Brazil. - Nogueira, João Miguel de Matos; San Martín, Guillermo (Beaufortia, 2002)
Eleven species of Syllis Lamarck, 1818 found in living coral heads of Mussismilia hispida (Verrill, 1868) in the State of São Paulo (Brazil) are reported and described, based on detailed analysis under stereo-, light, and scanning electron microscopes. Comments on the identity of each species are provided. The species are: S. beneliahuae (Campoy & Alquézar, 1982), S. corallicola Verrill, 1900, S. glandulata n. sp., S. gracilis Grube, 1840, S. hyllebergi (Licher, 1999), S. lutea (Hartmann-Schröder, 1960), S. maryae San Martín, 1992, S. prolifera Krohn, 1852, S. pseudoarmillaris n. sp., S. truncata Haswell, 1920, and S. tyrrhena (Licher & Kuper, 1998). Syllis glandulata n. sp. and S. pseudoarmillaris n. sp. are herein described. Except for S. gracilis, S. prolifera, and S. corallicola, this is the first report for all those species from Brazilian waters. Syllis hyllebergi is reported for the first time after the original description.
World Polychaeta Database (WPolyDb) World Polychaeta Database (WPolyDb)